1998
DOI: 10.1111/j.2044-8279.1998.tb01272.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐level analysis of cultural experience and gender influences on causal attributions to perceived performance in mathematics

Abstract: The findings do not concur with research findings from Western and Asian countries where Effort is considered important in making attributions for either perceived success or failure. The findings, however, agree with research findings from Asian and other non-Caucasian societies where success is attributed to external factors (e.g., task difficulty) and failure to internal factors (e.g., ability). These findings have some implications for cross-cultural research in causal attribution as it relates to academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The preference toward nonstudiousness and athleticism over studiousness and nonathleticism was discovered in the previous studies, as well (see Carrington & Bailey, 1999;Cramond & Martin, 1987;and Tannenbaum, 1962, for details). Our results also supported Kivilu and Rogers' (1998) negation of the traditional belief that effort is valued more than any other causal attribution, including ability, in Asian cultures. Moreover, as indicated, the Korean teachers did not show any preference toward academic brilliance over being average in school.…”
Section: Discussionsupporting
confidence: 81%
“…The preference toward nonstudiousness and athleticism over studiousness and nonathleticism was discovered in the previous studies, as well (see Carrington & Bailey, 1999;Cramond & Martin, 1987;and Tannenbaum, 1962, for details). Our results also supported Kivilu and Rogers' (1998) negation of the traditional belief that effort is valued more than any other causal attribution, including ability, in Asian cultures. Moreover, as indicated, the Korean teachers did not show any preference toward academic brilliance over being average in school.…”
Section: Discussionsupporting
confidence: 81%
“…Self-beliefs and attributions regarding success and failure are significantly related to achievement (House, 2003;Kivilu & Rogers, 1998;McMillan & Forsyth, 1981). College students facing academic failure are threatened with the harmful consequences that come with that failure and which may affect their self-esteem, confidence, and mastery of the academic material.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Literature in the field of attribution theory suggests a relationship between the way students explain the causes of their academic performance and academic achievement (House, 2003;Kivilu & Rogers, 1998;McMillan & Forsyth, 1981). Researchers have reported that attributions can influence how individuals react to success and failure on achievement-type tasks.…”
mentioning
confidence: 97%
“…According to Weiner (1974Weiner ( , 1986, a child may attribute test results to several factors, including ability or effort, assistance from the teacher, and the difficulty level of the test. Furthermore, prior research indicates that different attribution patterns have been identified for successful and unsuccessful students (Kivilu & Rogers, 1998;McMillan & Forsyth, 1981). These attributions differ from one another in three primary ways: locus, stability, and controllability (Weiner, 2000).…”
Section: Attribution and Academic Achievementmentioning
confidence: 97%